Utilizing Four Square Writing Method in Improving Students’ Essay Writing Skill - Muh. Agus Wijaya; Sri mulyani; Nurwahida Nurwahida (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
This research aimed to (1) find out whether or not the Four Square Writing Method is able to advance students’ essay writing skill, and (2) find out the students’ perceptions of the application of this method. This research was quantitative with pre-experimental design. The participants were nineteen students of the fifth-semester of the English Education Department at Institut Parahikma Indonesia. Based on the statistical analysis of the tests, the average of pre-test was 43.15, and the average of post-test was 62.57. The significant value of the tests was .000 < .05. It indicated that there was a significant difference between the scores of the tests in students’ essay writing before and after treatment. Furthermore, t-count was higher than t-table, 10.47 > 2.101. It implied that students’ essay writing was improved after doing treatment by using this method. This research also revealed students’ perceptions of the use of FSWM. 63.2% of the students claimed that it was interesting to be implemented in teaching writing, and 57.9% of them agreed that this method was effective to be implemented in writing an essay, but 10.5% of them stated that it was slightly helpful to improve their writing. Besides, when asked about obstacles in the implementation of this method, 26.3% of the students agreed that it was difficult to use; 21.1% of them said that it required too many steps to write, and 5.3% of them stated that they could not focus on writing when using it. Interestingly, 47.7% of them agreed that there were no obstacles in using it. Therefore, it can be concluded that this method could assist students in improving students’ essay writing skill. Based on the findings of this research, it is recommended that the teacher consider to use Four Square Writing Method as one of methods in teaching writing.